Determination of elastomer content in NR/SBR/BR blends - Alexandra Helena de Barros; Rachel Farias Magalhães; Lídia Mattos Silva Murakami; Milton Faria Diniz; Natália Beck Sanches; Taynara Alves de Carvalho; Jorge Carlos Narciso Dutra; Rita de Cássia Lazzarini Dutra (Polímeros)
Abstract Determining elastomer content in ternary rubbers via infrared (IR) spectroscopy presents challenges due to spectral band overlap.Coupled techniques could be a solution, but in certain cases it can also involve overlapping events resulting in greater errors. The best option is to use an instrumental technique with appropriate conditions that avoid overlapping. This paper presents the development of transmission/reflection IR methodologies for the content determination of a blend with natural rubber, styrene-butadiene copolymer, and polybutadiene (NR/SBR/BR), with A887 and A1375 bands for NR and A699 for SBR. The BR content, which was calculated by subtraction of the NR and SBR results from the IR methodology, is confirmed by acid-resistance quantitative data. The methodologies errors (2 to 6%), with non-overlapping bands, encompass what is found in the literature (5%). Such development ensures the determination of elastomer content in ternary rubbers with fast and accurate methodologies.